Systemic Delivery of Microencapsulated 3-Bromopyruvate for the Therapy of Pancreatic Cancer - Chapiro, Julius (Clin Cancer Res, 2014)
PURPOSE: This study characterized the therapeutic efficacy of a systemically administered formulation of 3-bromopyruvate (3-BrPA), microencapsulated in a complex with β-cyclodextrin (β-CD), using an orthotopic xenograft mouse model of pancreatic ductal adenocarcinoma (PDAC). EXPERIMENTAL DESIGN: The presence of the β-CD–3-BrPA complex was confirmed using nuclear magnetic resonance spectroscopy. Monolayer as well as three-dimensional organotypic cell culture was used to determine the half-maximal inhibitory concentrations (IC(50)) of β-CD–3-BrPA, free 3-BrPA, β-CD (control), and gemcitabine in MiaPaCa-2 and Suit-2 cell lines, both in normoxia and hypoxia. Phase-contrast microscopy, bioluminescence imaging (BLI), as well as zymography and Matrigel assays were used to characterize the effects of the drug in vitro. An orthotopic lucMiaPaCa-2 xenograft tumor model was used to investigate the in vivo efficacy. RESULTS: β-CD–3-BrPA and free 3-BrPA demonstrated an almost identical IC(50) profile in both PDAC cell lines with higher sensitivity in hypoxia. Using the Matrigel invasion assay as well as zymography, 3-BrPA showed anti-invasive effects in sublethal drug concentrations. In vivo, animals treated with β-CD–3-BrPA demonstrated minimal or no tumor progression as evident by the BLI signal as opposed to animals treated with gemcitabine or the β-CD (60-fold and 140-fold signal increase, respectively). In contrast to animals treated with free 3-BrPA, no lethal toxicity was observed for β-CD–3-BrPA. CONCLUSION: The microencapsulation of 3-BrPA represents a promising step towards achieving the goal of systemically deliverable antiglycolytic tumor therapy. The strong anticancer effects of β-CD–3-BrPA combined with its favorable toxicity profile suggest that clinical trials, particularly in patients with PDAC, should be considered.